The Epistle of the eloquent clarification concerning the refutation of Ibn Qutayba - Nuʻmān ibn Muḥammad, Abū Ḥanīfah, -974 (Islamic history and civilization ;, 2012)
This book offers an early Shiite/Fatimid controversy against Sunnite scholars in matter of Islamic law. Al-Qadi al-Nu'man (d. 363/974) refutes Ibn Qutayba's (d. 276/889) argument according to which succinct legal formulas exempt civil servants from the need of long dissertations of jurists.